Characterization of the HLA-A2.2 subtype: T cell evidence for further heterogeneity. - Gotch, F; Kelly, C; Ellis, SA; Wallace, L; Rickinson, AB; van der Poel, J; Crumpton, M; Mcmichael, A (Springer-Verlag, 1985)
Five blood donors were identified whose HLA-A2 is different from the common HLA-A2. Their A2 molecule (A2.2) had a more basic isoelectric point than normal A2 (A2.1). Cytotoxic T lymphocytes (CTL) restricted by HLA-A2.1, specific for influenza A and Epstein-Barr viruses, failed to lyse virus-infected target cells with HLA-A2.2. Identical patterns were obtained with both viruses. CTL from four of the A2.2-positive donors recognized target cells prepared from others in the group that shared only the HLA-A2.2 antigen. The A2.2 antigen from one donor seemed to be different in that target cells were not recognized by CTL from donors with the normal A2.1 nor with basic A2.2. There seems, therefore, to be heterogeneity within the HLA-A2.2 subtype.